2007
DOI: 10.1002/qj.167
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of minor constituents in a cloudy atmosphere with remote-sensing millimetre-wave measurements

Abstract: ABSTRACT:The presence of clouds in remote-sensing measurements is often the cause of information loss about the minor atmospheric constituent profiles that are the goal of the measurement. Millimetre-and submillimetre-wave sounding can be used to abate the problems of cloud contamination. A quantitative assessment of this possibility is provided with the systematic simulation of the retrieval of minor atmospheric constituents in the presence of ice cirrus clouds of different density and particle size. The simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The largest absorption observed in Fig. 12 around scan 12 corresponds to clouds that in the retrieval study of Del Bianco et al (2007) were located close to the boundary between case 2 and 3.…”
Section: Retrieval Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The largest absorption observed in Fig. 12 around scan 12 corresponds to clouds that in the retrieval study of Del Bianco et al (2007) were located close to the boundary between case 2 and 3.…”
Section: Retrieval Resultsmentioning
confidence: 89%
“…So it is important to develop instruments that can avoid the attenuation of the cirrus clouds that are often present in the UTLS. Fortunately, the optical depth of cirrus clouds is not the same at all wavelengths (Warren, 1984): the relatively low extinction coefficient of ice particles at longer wavelengths (far infrared and millimetre wave spectral interval) can be exploited to measure the UTLS region also in presence of cirrus clouds (Del Bianco et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Turning to much longer wavelengths, in the millimeter wavelength region, a very useful region of high transparency is observed even for the most dense ice cirrus clouds. In a case study performed for the Millimetre‐wave Airborne Receiver for Spectroscopic Characterisation of Atmospheric Limb‐Sounding instrument [ Oldfield et al , 2001], which observes the atmospheric emission in the millimeter wave region with a spectral resolution of 200 MHz, Del Bianco et al [2007] have quantified the loss of information caused by ice clouds when making atmospheric composition measurements with this instrument. They showed that the effect of most clouds is adequately described with a model of atmospheric continuum absorption.…”
Section: Retrieval Of Atmospheric Composition and Clouds In The Firmentioning
confidence: 99%
“…KLIMA is an extension of a previous code called MARC (millimetre-wave atmospheric-retrieval code) [37] specifically developed for the millimetre-wave spectral region and limb geometry. The updated version of this code, KLIMA, can be used in various geometrical configurations (limb [38,39], zenith [40] and nadir [23,[41][42][43][44]) and spectral bands (from millimetre and sub-millimetre wave [37] to near-infrared [45]). Finally, the KLIMA code was also used to simulate the nadir and limb radiances for a Martian atmosphere in the context of some internal tests related to the planetary Fourier spectrometer (PFS) instrument on board of Mars express (MEx) [11] and compared with the simulations obtained using the code described by Ignatiev et al [20].…”
Section: The Klima Codementioning
confidence: 99%